Types and Motifs in The Folktale of Sawunggaling in Surabaya (NOBEL: Journal of Literature and Language Teaching, 2017)
The folktale of Sawunggaling is one of the forms of folktale in East Java, particularly, in Surabaya. The folktale of Sawunggaling for the people of Surabaya is a story which has mythological, historical and educational values. This study is focused on the types and motifs in the Folktale of Sawunggaling. This study is different from the previous research which has been done by previous researchers. This research is aimed to find out what types and motives which are contained in the folktale of Sawunggaling. This research is a qualitative research using descriptive analysis method. The types and motifof the folktale of Sawunggaling are classified and categorized by using the type index of Antti Aarne and the motifindex of Stith Thompson. Antti Aarne proposed five types of tales namely Animal Tales, Ordinary Tales, Jokes and Anecdotes, Formula Tales, and Unclassified Tales only one which is contained in the folktale of Sawunggalingi.e. the Ordinary Tales. Meanwhile, 9 motifs in the folktale ofSawunggalinghave been found by using the motif of Stith Thompson.